Devaluation of manat: expectations and realities - Gubad Ibadoghlu (ZBW - Leibniz Information Centre for Economics, 2024)
This article will examine eight factors and evaluate the probability of Azerbaijan's manat devaluation in the post-oil period. However, there is no proportionality between the degree of influence of the listed factors and their ranking.
Keywords: 330; devaluation; inflation; PPP; manat; foreign trade; current account balance; REEM; bank; HHI